Current status of the QUBIC experiment - Scoccola, Claudia Graciela; Almela, Daniel Alejandro; Arnaldi, Luis Horacio; Aumont, J.; Azzoni, S.; Banfi, S.; Bélier, B.; Battistelli, E. S.; Baú, A.; Cobos Cerutti, Agustin Cleto; Duca, Clara; Etchegoyen, Alberto; et al. (Asociación Argentina de Astronomía, 2021)
Fil: Scoccola, Claudia Graciela. Universidad Nacional de La Plata. Facultad de Ciencias Astronómicas y Geofísicas; Argentina